Integrating National Identity and Global Competence in Indonesia’s Hybrid Curriculum: A Systematic Literature Review - Khairul Azmi; Kalayo Hasibuan (Faculty of Education and Teacher Training of UIN Palopo, 2026)
The adoption of an international curriculum in Indonesian schools creates a conceptual tension between the formation of national identity and the need for global competency development. Although the practice of hybrid curriculum is becoming more widespread, research findings are still fragmented and have not provided an adequate theoretical foundation to reconcile the two orientations. This study uses a Systematic Literature Review (SLR) with a thematic-conceptual synthesis approach to analyze the integration of national and international curricula. The search was conducted on Google Scholar, with a limit of 2016–2025. Out of a total of 127 initial recordings, 18 peer-reviewed articles met the eligibility criteria and were analyzed to map the pattern of curriculum integration and value orientation brought. The analysis identified three main integration models: additive (9 studies), subtractive (5 studies), and transformational (4 studies). The additive model shows the dominance of the practice of adding international curricula without recontextualizing grades, resulting in the fragmentation of learning objectives. The subtractive model shows the dominance of global epistemology that weakens the space for the articulation of national values. Meanwhile, transformational models, although at least quantitatively, show the highest level of coherence through the reconstruction of global competencies based on national values. A systematic review of 18 studies shows that the most sustainable curriculum integration practice and in line with the mandate of national identity formation, is a transformational model, as it links global competencies to the foundation of national values epistemologically and pedagogically. Follow-up studies are recommended to test the application of this model in the context of classroom learning and integrated assessment design.